1992
DOI: 10.1002/maco.19920431202
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Chloriden auf die Oxidation des 2¼ Cr‐1 Mo‐Stahls

Abstract: Der Einfluß von auf die Zunderschichten aufgebrachten NaCl‐Ablagerungen auf die Oxidation des 2¼ Cr‐1 Mo‐Stahls wurde bei 450 °C–650 °C untersucht. Die Anwesenheit von NaCl führt zu stark beschleunigter Oxidation unter Bildung poröser und rissiger Fe2O3‐Schichten, sowie von festem FeCl2 an der Metall/Oxid‐Grenzfläche. Durch Reaktion des Chlorids mit der Zunderschicht entsteht Cl2, das in die Schicht eindringt und an der inneren Phasengrenze FeCl2 bildet, dieses verdampft stetig und wird dann bei der Diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Since gaseous reaction products, CrCl 2 and CO, are formed, holes are left in the metal matrix and internal oxidation follows. Other carbides such as Mo 6 C, TiC and NbC are more corrosion resistant than the alloy matrix and stay uncorroded. Accordingly, presence or formation of chromium carbides should be avoided in alloys applied in oxidizing-chloridizing environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since gaseous reaction products, CrCl 2 and CO, are formed, holes are left in the metal matrix and internal oxidation follows. Other carbides such as Mo 6 C, TiC and NbC are more corrosion resistant than the alloy matrix and stay uncorroded. Accordingly, presence or formation of chromium carbides should be avoided in alloys applied in oxidizing-chloridizing environments.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the scale indicates that the mechanism of the scale growth is the same: formation of a multilayer by active oxidation, repeated cracking and spalling of the layers and formation of oxide bubbles over cracks. The metal phase contains intermetallic compounds Cr 6 Fe 18 Ti 5 as precipitates and they are preferentially attacked, due to the highly negative free energies of Ti-chlorides formation.…”
Section: 3ternary Alloys Fe-15% Cr-mmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxides can be dissolved in molten NaCl-KCl also by acidic and basic dissolution. The effect of solid chlorides like KCl, NaCl, MgCl 2 and CaCl 2 on corrosion of alloy steels has been investigated by Reese and Grabke [6,7]. Their experiments in He -O 2 and He -O 2 -SO 2 atmospheres at 500 and 700 8C have shown that the salt reacts with the oxide scale of the pre-oxidised sample forming ferrate or chromate and releasing chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…As chlorine is not consumed in this process, it plays a catalytic role. Reese and Grabke [6] have shown by thermogravimetric studies that evaporation of FeCl 2 from the metal-scale interface is the rate determining step in 'active oxidation'.…”
Section: Introductionmentioning
confidence: 99%